Allicin and total phenolic content and antioxidant activity in conventional and organic garlic - Wongsa P. (2017)
Consumers who are interested in a healthy life style are creating a demand for foods rich in natural biologically active compounds. Garlic is a source of many bioactive phytochemicals including polyphenolic and organo-sulfur compounds. This study evaluated allicin content, total phenolic content and antioxidant activity of softneck garlic (Allium sativum var. sativum) and hard-neck garlic (Allium sativum var. ophioscorodon) and studied the influence of genotype and agronomical practice on garlic. Garlic samples were obtained from different genotypes, agronomical practices and locations. Significant differences were observed in allicin content, total phenolic content and antioxidant activity between garlic genotypes, agronomical practices and locations. The amount of allicin varied from 4.5 to 26.8 mg g -1 dw, total phenolic compounds ranged from 1.5 to 4.7 mg GAE g -1 dw and antioxidant activity varied from 7.2 to 40.2%. A moderate positive correlation was found between total phenolic content and antioxidant activity. The difference in allicin concentration between genotypes and agronomical practices was significant. Total phenolic content was not significantly different between genotypes but was significantly impacted by the agronomical practices.